In Vitro Identification of Novel Plasminogen-Binding Receptors of the Pathogen Leptospira interrogans - Vieira, Monica L.; Atzingen, Marina V.; Oliveira, Tatiane R.; Oliveira, Rosane; Andrade, Daniel M.; Vasconcellos, Silvio A.; Nascimento, Ana L. T. O. (PLOS ONE, 2010)
Background Leptospirosis is a multisystem disease caused by pathogenic strains of the genus Leptospira. We have reported that Leptospira are able to bind plasminogen (PLG), to generate active plasmin in the presence of activator, and to degrade purified extracellular matrix fibronectin. Methodology/Principal Findings We have now cloned, expressed and purified 14 leptospiral recombinant proteins. The proteins were confirmed to be surface exposed by immunofluorescence microscopy and were evaluated for their ability to bind plasminogen (PLG). We identified eight as PLG-binding proteins, including the major outer membrane protein LipL32, the previously published rLIC12730, rLIC10494, Lp29, Lp49, LipL40 and MPL36, and one novel leptospiral protein, rLIC12238. Bound PLG could be converted to plasmin by the addition of urokinase-type PLG activator (uPA), showing specific proteolytic activity, as assessed by its reaction with the chromogenic plasmin substrate, D-Val-Leu-Lys 4-nitroanilide dihydrochloride. The addition of the lysine analog 6-aminocaproic acid (ACA) inhibited the protein-PLG interaction, thus strongly suggesting the involvement of lysine residues in plasminogen binding. The binding of leptospiral surface proteins to PLG was specific, dose-dependent and saturable. PLG and collagen type IV competed with LipL32 protein for the same binding site, whereas separate binding sites were observed for plasma fibronectin. Conclusions/Significance PLG-binding/activation through the proteins/receptors on the surface of Leptospira could help the bacteria to specifically overcome tissue barriers, facilitating its spread throughout the host.